Pengaruh Persepsi Kemudahan, Kepercayaan dan Inovasi Terhadap Kepuasan Penumpang Bus Trans Batam - Siti Maryam; Tiurniari Purba (Komunitas Dosen Indonesia, 2023)
This research is intended to find out how perceptions of convenience, trust and innovation influence the satisfaction of Trans Batam bus passengers. In conducting this research, it can use a population which can total 73,739 passengers which can come from the number of passengers in November 2022. In carrying out data testing, several data analysis techniques can be used which can include validity tests and reliability tests as data quality tests, in the normality test, the multicollinearity and heteroscedasticity tests function as tests of classical assumptions, in multiple linear regression analysis and analysis of the coefficient of determination (R2) can function as tests of influence, the t test and f test can function as hypothesis testing. The findings of the study found that perceived convenience can have a partial, positive and significant effect on passenger satisfaction with an effect size of 20.6%, trust can have a partial, positive and significant effect on passenger satisfaction with an influence size of 28.7%, innovation can give a partial positive and significant effect on passenger satisfaction with an influence size of 32.3%, perceived convenience, trust and innovation can have a simultaneous positive and significant influence on passenger satisfaction with an influence size of 75.8%.